2012
DOI: 10.3233/wor-2012-0540-2893
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent cognitive task may improve motor work performance and reduce muscle fatigue

Abstract: Performance of certain cognitive tasks either during physical load or in rest pauses between boosts might lead to slowing of muscle fatigue and fatigue related decline in performance. Seventeen right-handed healthy volunteers (age 24±1.4, 8 males) participated in this study, aiming to investigate the effect of the level of the cognitive information processing -1) passive perception of audio stimuli, 2) active stimuli discrimination, 3) active stimuli discrimination following motor response -on motor task perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…However, in these three studies, endurance performance was unchanged compared to a simple mental‐math task condition. In the present study, the 1‐back condition did not induce a distraction effect (i.e., performance improvement by diverting subject’s attentional focus from pain/fatigue perceptions), as observed in some studies (Cruz‐Montecinos et al, ; Evstigneeva et al, ). In addition to its nonself‐regulated nature, our task may thus be more demanding in the context of CMDT as compared to a simple mental‐math task.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, in these three studies, endurance performance was unchanged compared to a simple mental‐math task condition. In the present study, the 1‐back condition did not induce a distraction effect (i.e., performance improvement by diverting subject’s attentional focus from pain/fatigue perceptions), as observed in some studies (Cruz‐Montecinos et al, ; Evstigneeva et al, ). In addition to its nonself‐regulated nature, our task may thus be more demanding in the context of CMDT as compared to a simple mental‐math task.…”
Section: Discussionsupporting
confidence: 81%
“…Contemporary research showed that the addition of a cognitive task to a motor task impaired endurance time (Keller-Ross et al, 2014;Mehta & Agnew, 2012;Pereira et al, 2015;Yoon et al, 2009). In contrast, other research found preserved (Shortz & Mehta, 2017;Vanden Noven et al, 2014) or even increased (Cruz-Montecinos et al, 2018;Evstigneeva, Aleksandrov, Mathiassen, & Lyskov, 2012) endurance time when motor task was realized concomitantly to a cognitive task. Such discrepancies may be related to the complexity of the cognitive task (i.e., level of difficulty or self-regulated cognitive task) as well as the nature of the motor task (i.e., muscle involved, contraction intensity, sustained vs. intermittent contraction), which certainly influences the extent of changes in endurance time.…”
Section: Introductionmentioning
confidence: 86%
“…Four high-quality CCTs provided moderate evidence for the positive effect of task variation in reducing fatigue of the upper extremities or the whole body. Three studies (Evstigneeva, Aleksandrov, Mathiassen, & Lyskov, 2012; Luger, Bosch, Hoozemans, Veeger, & de Looze, 2016; Mathiassen, Hallman, Lyskov, & Hygge, 2014) that involved subjective ratings showed promising results. One study (Luger, Bosch, Hoozemans, de Looze, & Veeger, 2015) provided evidence of no effect based on the median frequency and amplitude of EMG.…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of sustained vocal encouragement, motivational self-talk, motivational music and video on the power output during the maximal effort exercising (St. Clair Gibson and Noakes, 2004 ; Barwood et al, 2009 , 2015 ) suggests the involvement of motivation and effort perception in regulation of maximal force output under different environmental conditions. Evstigneeva et al ( 2012 ) reported that the button pressing in response to the rare deviant acoustic stimuli during the fatiguing task (sustained submaximal contraction) resulted in improved motor task performance, compared to the passive listening task.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that diversity and variation of muscle load alleviated fatigue caused by sustained or monotonous repetitive work (Mathiassen, 2006 ). The performance of a cognitive task (auditory choice reaction task) simultaneously with a fatiguing motor task (sustained submaximal contraction) results in improved performance of the motor task in comparison with the passive listening task (Evstigneeva et al, 2012 ). We can assume that at least some of these processes are associated with attention.…”
Section: Introductionmentioning
confidence: 99%